Mu-opioid receptor expression in multibacillary leprosy - Patrícia Elizabeth Pignataro; Leonardo Pereira Quintella; Helen Ferreira; Adelaide Lopes Amorim; Roberta Olmo Pinheiro; Luiz Claudio Ferreira; Francisco das Chagas de Carvalho Rodrigues; Maria Inês Fernandes Pimentel (Open Journal of Tropical Medicine - Peertechz Publications, 2019)
Background: During the clinical course of multibacillary leprosy disease, mainly in Lepromatous Leprosy (LL) patients, acute and systemic inflammatory episodes known as Erythema Nodosum Leprosum (ENL) may be present. The histology of ENL skin lesions initially shows hyperplasia of epidermis followed by a neutrophilic inflammatory process. Sensory neurons and keratinocyte communicate in paracrine way via molecules such as neuropeptides, cytokines, and opioids. Previous studies demonstrated that opioids might cause immunosuppression through Mu Opioid Receptor (MOR).  Objectives: To verify the expression of MOR in leprosy multibacillary patients with and without ENL.  Methods: Cutaneous lesions from fifteen patients with LL with no reaction and 18 patients with ENL from Oswaldo Cruz Foundation, Brazil, were studied. Immunohistochemistry reaction with anti-MOR antibody was performed in paraffin embedded skin lesions biopsy. Results: Forty-six percent of LL patients without reactional episodes presented positivity for MOR in keratinocytes while in the ENL group 88.9% presented strong staining in epidermis (p=0.02), In lepromatous lesions, almost all macrophages were positive for MOR, in contrast to the rare positivity in ENL macrophages.  Main Conclusions: The data presented here suggest the involvement of MOR in the immunomodulation of ENL.